The Voice of Cognition: Active and Passive Voice Influence Distance and Construal. (April 2020) - Chan, Eugene Y.; Maglio, Sam J.
English passages can be in either the active or passive voice. Relative to the active voice, the passive voice provides a sense of objectivity regarding the events being described. This leads to our hypothesis that passages in the passive voice can increase readers' psychological distance from the content of the passage, triggering an abstract construal. In five studies with American, Australian, British, and Canadian participants, we find evidence for our propositions, with both paragraphs and sentences in the passive voice increasing readers' felt temporal, hypothetical, and spatial distance from activities described in the text, which increases their abstraction in a manner that generalizes to unrelated tasks. As such, prose colors how people process information, with the active and passive voice influencing the reader in ways beyond what is stated in the written word.